Does Surgical Approach in Pelvic Floor Repair Impact Sexual Function in Women?. Issue 4 (11th September 2019) - Zawodnik, Astrid; Balaphas, Alexandre; Buchs, Nicolas Christian; Zufferey, Guillaume; Robert-Yap, Joan; Buhler, Leo H.; Roche, Bruno; Ris, Frédéric
Abstract: Introduction: Surgical routes used to correct complex pelvic floor disorders (CPFDs) may have a negative impact on women's sexual function. Currently, there is no evidence concerning the impact of a specific surgical procedure on postoperative sexual function in women. Aim: The aim of this study was to compare an abdominal approach with rectopexy and sacrocolpopexy to a perineal procedure with abdominal rectopexy, regarding female sexual function in cases of CPFDs. Methods: Women who were operated for CPFDs between January 2003 and June 2010 were retrospectively asked to answer the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire-12, the Miller Score of Incontinence, and a urinary incontinence frequency score. We also questioned them about their sexual function and satisfaction before and after the operation using visual analogic scores. Main Outcome Measure: We compared the Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire-12 before and after the surgery in both groups, and we made an intragroup comparison. Results: There were 334 women identified, but only 51 could be included. Globally, we found no statistically significant differences in terms of sexual function before and after surgery between the 25 groups. Intragroup comparison demonstrated that, within the perineal approach group, patients experienced a decrease in their sexual arousal after the procedure. The choice of surgical route for pelvic floor disorders does not seem to have an impact on the results of postoperative sexual function in women. This study adds to the limited literature on sexual outcomes of surgery for CPFD. It is limited principally due to its retrospective design and the small number of patients included. Conclusion: Both surgical routes have very similar outcomes on most sexual questions. A perineal approach combined with abdominal rectopexy did, however, demonstrate a slight decrease in sexual arousal of the patients after the intervention.